Intergenerational complexes in analytical psychology : the suffering of ghosts - Kimbles, Samuel L. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book shows how the cultural unconscious with its multiple group dynamics, identities (racial, ethnic, gender, nationalities, seething differences of conflicts, polarizations, individual personalities are organized by cultural complexes and narrated by archetypal story formations which the author calls phantom narratives"--
OCLC-licensed vendor bibliographic record.
Keywords: Intergroup relations; Jungian psychology; Intergenerational relations -- Psychological aspects; Social conflict -- Psychological aspects; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Movements / Jungian